New Vernacular Architecture: Experimental Construction Site in Bärnau, Bavaria - Julius Schönberger (Journal of Traditional Building, Architecture and Urbanism)
This experimental construction site in Bärnau, a small town on the border between the Czech Republic and Germany, explores innovative approaches to vernacular architecture through a prism of sustainability, craftsmanship, and regionalism. The project addresses three key questions. First, how can we learn from historical building methods and materials to build more sustainably while maintaining social and regional relevance? Second, how to revitalize traditional craftsmanship, focusing on making local materials and techniques more attractive to ensure the preservation of valuable knowledge? Lastly, what potential is there for creating buildings with minimal environmental impact using only regional materials, thereby supporting local economies and ecological integrity?